Determinants of problem sports betting among college students: moderating roles of betting frequency and impulsive betting tendency - Yawen Shen (BMC Psychology, 2023)
Abstract Purpose Given the risk and increased incidence of problem betting for young adults, the purpose of the current study was to understand what influences college students’ problem sports betting behavior using the theory of planned behavior (TPB). Methods An institutional-based cross-sectional study was conducted. Data were collected from 311 college students in the U.S. using a survey questionnaire and primarily analyzed using the partial least squares structural equation modeling (PLS-SEM) technique to investigate the relationships between the study variables. In addition, multi-group SEM analyses were conducted to investigate the moderating roles of betting frequency and impulsive betting tendencies regarding sports betting. Results The results suggested that college students’ sports betting intentions (SBI) were associated with attitude towards sports betting, motivation to comply with others, and subjective norm, in this order, but not with perceived behavioral control (PBC). Problem sports betting (PSB) was significantly positively related to their SBI and negatively correlated with PBC. In addition, multigroup analyses found the moderating roles of betting frequency and impulsive betting tendency, especially in the relationship between SBI and PSB. The SBI-PSB relationship was stronger with the infrequent/low-betting group and low-impulse betting group, compared to the frequent/high-betting and high-impulse betting group. Conclusion Overall, the results highlighted the importance of peer influence and attitude formation concerning sports betting. Recognizing what influences PSB and the roles of habitual and impulse sports betting in this population are recommended in developing proper public health programs to mitigate PSB issues.